Growth performance of Tectona grandis Linn F. between two thinning operations at Shankarnagar, western Terai, Nepal - Thapa, HB; Gautam, SK (Banko Janakari, 2009)
Tectona grandis plot was established on 7th July 1992 in 0.50 hectare at a spacing of 2.5m x 2.5m at Shankarnagar, Rupandehi district, in the western Terai of Nepal. Estimated average fresh wood production of 14.5 years old teak was found to be 226 kg (201 tons ha-1) before thinning and 125 kg (53 tons ha-1) in thinned trees and 318 kg (148 tons ha-1) for trees after thinning. Above ground green biomass was estimated to be 134 kg tree-1 (57 tons ha-1) for thinned trees, 240 kg tree-1 (214 tons ha-1) for trees before thinning and 337 kg tree-1 (157 tons ha-1) for trees after thinning. Prior to thinning, the mean over bark stem volume was 0.2313 m3. In thinning, 59 m3 per ha-1 volume was removed. The volume of standing trees before thinning at 14.5 years was 206 m3 ha-1. After thinning, per unit and mean basal area, biomass and over bark stem volume has been increased considerably during 7-years from 7.5 years to 14.5 years. Shankarnagar Community Forest User Group has earned NRs. 60,000.00 by selling thinned yield i.e. poles and fire wood Keywords: Tectona grandis, growth, biomass, volume, rotation, thinning, Nepal doi: 10.3126/banko.v17i2.2151 Banko Janakari, Vol. 17, No. 2, 11-17